Sociálna kvalita a sociálna ekonomika - Antalová, Mária; Pongráczová, Eva (Univerzita Pardubice, 2011)
There exists developed theory of the social quality on ontological and epistemological level, which is accepted as political project of the European Union. This strategy is possible to achieve with supported tools of other policies, for instance social policy and in its frame social economics. At present time social economics is developing and forming as scientific discipline and its mission helps to implementate the social quality at mega and national level. Therefore is important to definite the relationship between these two categories.
Keywords: social quality; social economics; social enterprise; quality of life; social inclusion; social cohesion